2014
DOI: 10.1177/1757177414560249
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the International Nosocomial Infection Control Consortium (INICC) Multidimensional Hand Hygiene Approach, over 8 years, in 11 cities of Turkey

Abstract: Aims: To evaluate the effectiveness of the International Nosocomial Infection Control Consortium (INICC) Multidimensional Hand Hygiene Approach in Turkey and analyse predictors of poor hand hygiene compliance.Design: An observational, prospective, interventional, before-and-after study was conducted from August 2003 to August 2011 in 12 intensive care units (ICU) of 12 hospitals in 11 cities. The study was divided into a baseline and a follow-up period and included random 30-minute observations for hand hygien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…11 Furthermore, our findings were in consonance with other studies which used multi-interventional approaches with administrative support in ICUs. 12,13 Administrative support had a positive effect on efforts improving HH adherence. 14 Education and training were also included, which were identified by other researchers as an important HH promotive activities improving HCWs compliance.…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, our findings were in consonance with other studies which used multi-interventional approaches with administrative support in ICUs. 12,13 Administrative support had a positive effect on efforts improving HH adherence. 14 Education and training were also included, which were identified by other researchers as an important HH promotive activities improving HCWs compliance.…”
Section: Discussionmentioning
confidence: 99%
“…An example is the International Nosocomial Infection Control Consortium (INICC) Multidimensional Hand Hygiene Approach (IMHHA), which includes administrative support, availability of supplies, education and training, reminders, process surveillance, and performance feedback. Previous studies have reported significant improvement in adherence to hand hygiene with the implementation of the IMHHA in ICUs in various countries [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 97%
“…According to the Global Human Development Index (HDI) (41) , approximately 85% (21/25) of the countries in which the studies included in this review occurred have a very high or high HDI (4)(5)(7)(8)13,(19)(20)(21)(23)(24)(25)(26)(27)(28)(29)(30)(31)(34)(35)(36)(37) . With respect to the medium and low HDI countries (4/25) (18,22,(32)(33) , all had a pre-intervention HH compliance of less than 30%, and a post-intervention compliance of less than 50%, except a study (18) (1/4) that reached 57% after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…When performed immediately and individually, it has influenced the performance of professionals by allowing the identification of barriers that interfere in the HH compliance and seek timely solutions, as well as to detect the types of opportunities and the reason for failures for HH, highlighting the protagonism of the subject, that is, the central role of the health professional in the process of learning (20,30) . However, collective feedback is also an important alternative, since it is in the collective exercise of the process of knowledge construction that one can favor learning and enable the transformation of praxis (13,(43)(44) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation